The concept of polycentricity in European spatial planning: reflections on its interpretation and application in the practice of spatial planning - Shaw, David; Sykes, Olivier (International planning studies, 2004)
The concept of polycentric development has emerged as one of the hallmarks of the emerging field of European spatial planning. It was one of the key principles in the European Spatial Development Perspective (ESDP), it has been frequently debated by academics, and it has been invoked by those engaged in spatial development policy making across the scales of multi-level governance in Europe. The concept is subject to multiple interpretations. This article argues that as well as being differentiated by spatial scale (vertical differentiation), the concept can also be differentiated horizontally by context. It is currently being interpreted and employed in at least three domains of meaning: in the emerging field of transnational spatial planning for Europe; in the practice of spatial development policy making at the various levels of multi-level territorial governance within Europe where planning occurs; and in an emerging academic discourse relating to European spatial planning. The article then focuses on the second domain where polycentricity is employed and has meaning ascribed to it, through a consideration of how the concept has been interpreted and applied in recent spatial planning initiatives in England. The article concludes that further 'bottom-up' comparative research and analysis is key to future research into the concept of polycentricity in European spatial planning.